The role of central banks and the political environment in financial stability : a literature review : Chile, Colombia, Japan, Portugal and the UK - Venter, Zoë (2019)
Financial instability and the subsequent credit crunches experienced by a number of countries following two decades of global structural reforms highlighted the importance of stabilizing credit supply and assigning a higher importance to financial stability. In this paper, I look at the independence of the Central Bank, the political environment and the impact of these factors on financial stability. I substantiate the literature review discussion with a brief empirical analysis of the effect of Central Bank independence on credit growth using an existing database created by Romelli (2018). The empirical results show that fluctuations in credit growth are larger for higher levels of Central Bank Independence and hence, in periods of financial instability or ultimately financial crises, Central Bank Independence would be reined back in an effort to reestablish financial stability.